Significance and characteristics of the connection between morphological variables and derived indicators of situation-related efficiency in elite junior basketball players for three basic types of players - Trninic, M.; Jelicic; M.Foretic, N. (Collegium Antropologicum, 2013)
The purpose of this research was to establish and explain the significance and characteristics of the connection of morphological variables and situation-related efficiency in basketball players for three basic types of players. Based on the obtained results, we can claim that the latent morphological structure is not significantly connected to the applied indexes of situation-related efficiency of players on the sample of guards and forwards. Further on, there is no significant influence of the morphological status on the situation-related efficiency of players in guard and forward positions. On the other hand, latent morphological structure is significantly connected to all five used indexes of situation-related efficiency of players on the sample of centres. In accordance with this, optimal morphological structure of centres in offence involves marked longitudinality, voluminousity and transversality of the skeleton with unmarked sub-skin adipose tissue. When referring to the index of the absolute situation-related efficiency of the centres in defence, it is evident that high quality centres, unlike low quality ones, are characterised by longitudinality and voluminousity. Further on, AEG index, which includes two previously mentioned indexes (AEO and AED), describe absolute situation-related efficiency of the players in offence and defence phase and both indicate that the morphological structure of high quality centres in both phases of the game consists of extreme longitudinality of the skeleton, voluminousity and transversality. In PPLC1 index, three out of four beta-ponders are significant and these are: longitudinality, voluminousity and transversality. Finally, in PPLC2 index, as well as in the previously mentioned PPLC1 index, high quality centres differ from low quality ones in morphological structure which includes marked longitudinality, voluminousity, transversality and unmarked level of sub-skin adipose tissue.